ANTIOXIDANT ACTIVITY OF COMPOUNDS ISOLATED FROM THE ROOT WOODS OF ERYTHRINA DROOGMANSIANA (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The aim of this study was to isolate, to characterize secondary metabolites from methanolic extract of the root woods of Erythrina droogmansiana and to assess the antioxidant activity of the crude extract and isolated compounds. The phytochemical study led to the isolation of 3-(3’,4’-methelenedioxyphenyl)-2,3-epoxypropanol (1), asperphenamate (2) and three flavonoids namely genistein, diadzein and 4’,5,7-trihydroxy-8-prenylisoflavone. These compounds were characterized using their 1H NMR, 13C NMR, HMBC, HSQC, COSY, mass spectral and the literature. To evaluate antioxidant activity of crude extract and isolated compounds, the radical scavenging (DPPH) and Ferric Reducing Ability Power (FRAP) were performed using ascorbic acid as standard. Compounds 1 and 2 showed moderate radical scavenging potential with IC50 value of 3.14 and 3.31 mg/ml respectively, and moderate reducing power ability with value of 0.14±0.01 mgAAE/mg and 0.21±0.01 mgAAE/mg respectively. The more active compound was genistein (3) with IC50 value of 1.96 mg/ml for the DPPH radical scavenging potential and 0.24±0.02 mgAAE/mg for its ability to reduce iron.